REFORMULASI HUBUNGAN AGAMA DENGAN NEGARA: DIALOG PEMIKIRAN YUSUF AL-QARDHAWY DENGAN ULAMA KLASIK TENTANG POLITIK KENEGARAAN DAN IMPLIKASINYA BAGI PERPOLITIKAN DI INDONESIA - Mashudi, Mashudi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
This research describes the formulation want state politics and religious ties with the country according to Yusuf al-Ulama Qardhawy and Classical. The results of the analysis of their thinking as outlined in his works, can be explained that Yusuf al-Qardhawy reformulate the concept of the relationship between religion and the state as well as the state political through and isti'ab syumuli method, a problem of how to resolve the impasse in state politics as well as the relationship between religion and state product classical scholars thought. Reformulation of the concept of the relationship between religion and the state is the solution to the stagnation (stagnation) patterns of thought classical scholars. The concept of state politics by Yusuf al-Ulama Classical Qardhawy and there are points in common with the Indonesian state politics in the context of the present though not totally, so that some can be implemented to control the practice of politics in Indonesia lately away from religious ethics.***Penelitian ini ingin menjelaskan formulasi politik kenegaraan dan hubungan agama dengan negara menurut Yusuf al-Qardhawy dan Ulama Klasik. Hasil analisis dari pemikiran mereka yang dituangkan dalam karya-karyanya, dapat dijelaskan bahwa Yusuf al-Qardhawy mereformulasi konsep hubungan agama dan negara serta politik kenegaraan tersebut melalui metode shumulī dan isti’ab, suatu cara menyelesaikan kebuntuan problematika politik kenegaraan serta hubungan agama dan negara produk pemikiran ulama klasik. Reformulasi konsep hubungan agama dan Negara tersebut merupakan solusi atas stagnasi (kejumudan) corak pemikiran ulama klasik. Secara teoritis, konsep politik kenegaraan menurut Yusuf al-Qardhawy dan Ulama Klasik terdapat titik kesamaan dengan politik kenegaraan Indonesia dalam konteks sekarang meskipun tidak secara total, sehingga sebagian dapat diimplementasikan untuk mengendalikan praktik perpolitikan di Indonesia yang akhir-akhir ini jauh dari etika agama.